P131 Myocardial Injury and Dysfunction during COPD Exacerbations. (14th November 2013) - Patel, ARC; Kowlessar, BS; Donaldson, GC; Mackay, AJ; Singh, R; Wedzicha, JA; Hurst, JR
Abstract : Introduction: Cardiac biomarkers of myocardial injury and dysfunction are commonly raised in patients hospitalised with COPD exacerbations and are independent predictors of mortality. The relevance of this to the majority of community-treated events has not previously been studied. Methods: We prospectively measured serum troponin T and N-terminal brain pro-natriuretic peptide (NT-proBNP) in 55 patients from the London COPD Cohort in the stable state, at exacerbation onset and thereafter at days 3 (n = 44), 7 (n = 39), 14 (n = 38), and 35 (n = 25) during recovery. Exacerbation assessments were undertaken within one week of symptom onset, prior to therapy, and defined by two consecutive days of new or increased respiratory symptoms on prospectively-completed daily patient diary cards requiring at least one major (dyspnoea, sputum purulence, sputum volume) and another major or minor symptom (coryza, wheeze, sore throat and cough). Results: Cardiac biomarkers rose from the stable state to exacerbation (mean ( ± SD) troponin T 0.012 ( ± 0.011) vs 0.017 ( ± 0.016) µg/L, p < 0.001; NT-proBNP 23.1 ( ± 39.2) vs 36.0 ( ± 56.5) pg/ml, p < 0.001). These increases were significantly higher in those with known IHD (n = 12) compared to those without IHD (n = 43) (mean ( ± SD) increase in troponin T 0.011 ( ± 0.009) vs 0.003 ( ± 0.006) µg/L, p = 0.003; NT-proBNP 38.1 ( ± 37.7) vs 5.9 ( ± 12.3) pg/ml, p < 0.001). Cardiac biomarkers did not fall during the initial five-week exacerbation recovery period (troponin T -0.0003µg/L/day (95% CI -0.0008 to 0.0004), p = 0.431; NT-proBNP -0.096 pg/ml/day (95% CI -0.631 to 0.438), p = 0.723). They remained more elevated in those with IHD (n = 12) than in those without IHD (n = 43) during the five week recovery period (troponin T AUC 0.368 ± 0.311 µg/L/35days vs 0.088 ± 0.174 µg/L/35days, p < 0.001; NT-proBNP AUC 1590 ± 2620 pg/ml/35days vs 279 ± 725 pg/ml/35days, p = 0.005). Longer exacerbations were associated with greater myocardial injury at exacerbation (higher serum troponin T) and the magnitude of change from the stable state (rho = 0.323, p = 0.027; rho = 0.390, p = 0.007 respectively). Conclusions: Myocardial injury and dysfunction is common and clinically significant during COPD exacerbations in those with underlying IHD and relates to exacerbation length. Alternative approaches to mitigate cardiovascular complications, in stable COPD and at exacerbation, require further study.